A study on data-driven impedance matching in four channels bilateral teleoperation - Ramli, Mohd Syakirin; Ahmad, Hamzah; Razali, Saifudin; Othman, Nur Aqilah; Daud, Mohd Razali; Irawan, Addie; Mohd Nizam, Md Isa (2019)
A teleoperator system comprised of dual robots namely the master robot controlled by the human operators, and remote slave robots which tracks the motion of master, where it concurrently transmits the environment’s force back to the human operator. Problems arose when there exists a mismatch in terms of system dynamics between master and slave manipulators, which consequently yields to a distorted transparency between both sides of the systems. Therefore, there is a need to overcome the said mismatch pattern in the overall closed-loop architecture. The main objective of this research is to design and develop control algorithms to drive both sides of the master and slave system to attain symmetrical impedance between them. By ensuring that both sides are symmetry, a good transparency is feasible. The proposed techniques was to introduce an equalizer or controller connected to the master manipulator. Then, by utilizing the model-free approach, namely the Fictitious-Reference-Iterative-Tuning (FRIT), the controller can then be properly tuned to obtain a good control performance. This project focused on the computational modeling where the proposed impedance matching algorithms have been investigated and analyzed utilizing the Matlab (Simulink) Software. There are several possible applications that can employ the control algorithms derived from this project. Obviously, underwater tele-robotics may find the proposed technique is beneficial since the model-free approach which dealt mainly on the measured input-output data in tuning procedure, can help to overcome the uncertainty that exists in the underwater environment. Besides, we also had investigated and analyzed the feasibility of this technique when working with multi-slave manipulators configuration. Hence, this open the opportunity for applications that utilize the multi-robots configurations such as in automotive or manufacturing industries. In general, it was found that a symmetric impedance between the master and slave manipulators attainable with the utilization of equalizer in the form of Laguerre network connected in feedback-loop to the master manipulator. This was also applicable for the case of single-master-multiple-slaves system, but additional passive decomposition algorithm must also be employed to treat the multi-slaves manipulators into the Locked and Shape subsystems.